Funkcjonalizm w teoriach marketingu - Otta, Wiesław (Wydział Prawa i Administracji UAM, 1978)
There are two important and urgent reasons for developing theoretical marketing concepts based on Marxist methodology of social sciences: 1) a rising demand for such concepts declared by the socialist economy, 2) the attitudes of western authors to the marketing are not adequate for socialist economy and as such they cannot be accepted. The author is criticising the functional concepts developed in the theories of marketing. He is also analizing the sources of functionalism in marketing thought and proving its inconsistency with Marxist methodology of social sciences.
Functionalism in Marketing Theories